Youth entrepreneur : Jalan pintas menuju Indonesia minim pengangguran - Khoiriyah, Ikhda Rofiqotul (Maliki Interdisciplinary Journal, 2023)
This article examines the role of young entrepreneurs in overcoming unemployment and driving economic growth in Indonesia. By highlighting the definition of unemployment, its causal factors, and the unemployment rate in Indonesia, this article highlights the positive role of young entrepreneurs in creating new jobs, advancing innovation, and reviving the local economy. The article also explores the factors that influence the millennial generation’s decision to become young entrepreneurs. By concluding that young entrepreneurs have a key role in creating positive change, this article underlines the importance of collaborative support from the government, private sector and educational institutions to help the development of young entrepreneurs, for sustainable and inclusive economic growth in Indonesia.